Electronic and Optical Properties of Graphene Adsorbed with Methanol Molecules: First-Principles Calculations (Journal of Atomic and Molecular Sciences, 2018)
Properties of methanol molecules adsorbed on graphene are studied theoretically and various adsorption geometrical structures, density of states as well as the optical properties are obtained by means of first-principles calculations. Electronic characteristics and optical properties of graphene are sensitive to the molecule adsorptions. It is found that band gap appears when the methanol molecules are adsorbed. The dielectric function, refractive index, extinction coefficient, absorption coefficient and the reflectivity are changed. In the case of one methanol molecule adsorption, the peaks for the imaginary of the dielectric function and the adsorption coefficient shift to the high energy region, and new peaks appear in the visible range. The maximum value of extinction coefficient rises, and new peaks appear in the visible range when two methanol molecules are adsorbed.